Apesar que o vida loka também ama: experiência afetiva de adolescentes inseridos no tráfico de drogas - Veloso, Aline Matheus (2015)
The theme of adolescence author of an offense has been present both in discussions of scientific body, as by the media, civil society and public policy, which now represents a major problem in the Brazilian social context. Despite de existence of literature on the subject, few surveys are dedicated to examine the dimension these adolescents's affection. Thus, the aim of this research is to make a psychosocial analysis of the affective experience of adolescents on drug trafficking. This perspective aims against the stigma and characterization of the humanity in these teens, from the criticism of naturalizing and simplistic views that reduce the complexity of the issue, based on the theory of Vygotsky's emotions and philosophy of Spinoza. The survey was conducted with three adolescents in compliance with socio-educational measures in open environment(Probation and Community Service). The methodology used was participative-action-research, and the procedures adopted the formation of a film club in the group meetings and photo shooting in the individual ones. Data show us the suffering experienced by adolescents, and the marginalization of affections after entering the drug traffic. It was also possible to analyze the drug trade has a management of emotions, from sad passions like anger and hatred. However, the affection also emerged as processing power, providing a space for reflection about the "world of crime". The discussions finalize on the sharing of field experience and reflection about the importance of affection in psychosocial intervention